Cutting force model for power skiving of internal gear. (August 2020) - Onozuka, Hideaki; Tayama, Fuminao; Huang, Yu; Inui, Masatomo
Abstract: In recent years, power skiving has been rapidly promoted as a highly efficient machining method for internal gears. Many researches have been performed to improve the machining accuracy and tool life. In the present study, a simulation model for the cutting area and cutting forces was developed with the aim of improving the machining accuracy and tool life in the power skiving process. During the power skiving of internal gears, the cutting direction, chip thickness, and effective rake angle have a complex relationship with the relative motion of the tool and workpiece. First, the cutting area and uncut chip thickness during the skiving process were analyzed by performing a simulation of the interference of a discretized cutting tool edge and workpiece surface. Then, a two-dimensional oblique cutting model was applied to cutting edge elements. The cutting forces for the edge elements were expressed using the cutting direction, uncut chip thickness, effective rake angle, and specific cutting force coefficients, which represent the characteristics of the cutting forces of the workpiece material. A method to identify the cutting force coefficients according to the effects of the change in the effective rake angle was proposed on the basis of time-averaged cutting forces measured via cutting tests with power skiving tool which has multiple cutting edges. An optimization method was used to minimize the error of the measured and simulated cutting forces when the radial depth of cut and the feed rate were varied. Finally cutting tests were performed in which the radial depth of cut was changed, and the simulated forces were compared with the measured values. The analytical cutting forces obtained using the proposed method exhibited good agreement with the experimental results with an error of 15 %.